2012
DOI: 10.1109/ted.2012.2223471
|View full text |Cite
|
Sign up to set email alerts
|

Compact Capacitance Model of Undoped or Lightly Doped Ultra-Scaled Triple-Gate FinFETs

Abstract: A charge-based compact capacitance model has been developed describing the capacitance-voltage characteristics of undoped or lightly doped ultra-scaled triple-gate fin field-effect transistors. Based on a unified expression for the drain current and the inversion sheet charge density, i.e., the Ward-Dutton linear-charge-partition method and the drain current continuity principle, all trans-capacitances are analytically derived. The developed capacitance model is valid in all regions of operation, from the subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The device model used for the simulations is based on the work published in [6][7][8] for the drain current I ds and the internal trans-capacitances C xy of Triple Gate FinFETs. In order to execute the algorithm flow of the proposed tool, the FinFET device model is implemented in Matlab.…”
Section: A Aging Analysis Of the Cmos Invertermentioning
confidence: 99%
See 1 more Smart Citation
“…The device model used for the simulations is based on the work published in [6][7][8] for the drain current I ds and the internal trans-capacitances C xy of Triple Gate FinFETs. In order to execute the algorithm flow of the proposed tool, the FinFET device model is implemented in Matlab.…”
Section: A Aging Analysis Of the Cmos Invertermentioning
confidence: 99%
“…The device [6][7][8] and HC degradation models [3,4] along with the algorithm that implements the reliability analysis are coded in Matlab.…”
Section: Introductionmentioning
confidence: 99%
“…Several dc and RF models have been proposed in the literature , as well as the so‐called artificial neural network approach . However, full compact models, which describe the FinFET static and dynamic behaviors, are still needed for analog design.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction: Fin field-effect transistors (FinFETs) are candidates for the sub-22 nm technology node because of the well-suppressed shortchannel effects (SCEs), high transcondutance and an ideal subthreshold swing [1][2][3]. To further reduce SCEs and improve gate control, promising device structures, such as FinFETs, have been developed widely [4][5][6]. Recent research on FinFET devices has reported the relationship between the work function and trap function [7], but few reports have discussed the influence of layout parameters such as fin width, fin height and the number of fins on the electrostatic characteristics of devices.…”
mentioning
confidence: 99%